PENGEMBANGAN KRITERIA DAN KLASIFIKASI TINGKAT DEGRADASI LAHAN PADA LAHAN KERING (STUDI KASUS: LAHAN KERING DI KABUPATEN BOGOR) - SUSANTO, BAMBANG (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011), 2012)
Developing of Criteria and Classification of Land Degradation Level on Dryland (Case Study: Dryland in Bogor Regency. Optimization of dry land utilization including in Bogor Regency is still an important issue. One of the causes is due to land degradation. At the moment, land degradation inventory is still resulting tentative acreages, since the criterion was different among institutions. This research aims to develop criterion (classes range) and to classify land degradation in dry land on reconaissance scale. It based on variabels affecting level of degradation. Data was collected on surveys for a case study. The data then was analyzed using some techniques, for instances cluster analysis, and discriminant analysis. This research was resulting three criterions (range of classes) for five variables determining level of land degradation, there were type of bed-rock, slope, conservation (P-value), silt percentage, land use/ vegetation, Pavailable, exchange Al, and H. This research also generated three levels of degradation for reconnaissance scale, there were (1) sligtly degraded land (score <16), (2) moderately degraded land (score in between 16-39), and (3) strongly degraded land (score more than 39).
Keywords: land degradation, classification, criterion